О влиянии жесткости ребер на колебания и устойчивость незамкнутых цилиндрических оболочек - Абрамович, Х.; Заруций, В.А. (Прикладная механика, 2010)
On numerical examples of analyzing the cylindrical shell, the effect of rib stiffness on the minimal natural frequencies and critical stresses are studied. The shell is assumed to be longitudinally compressed, non-closed and stiffened by the «quasi-regular» systems of longitudinal ribs. It is shown that existence of the revealed before effect of sharp decreasing of minimal natural frequencies of vibrations don’t depend on the ribs stiffness in the case of fixed modes and small number of ribs. На числових прикладах вивчено вплив жорсткості ребер на мінімальні власні час-
тоти коливань і критичні напруження в поздовжньостиснутих незамкнених циліндричних оболонках,
підсилених «квазірегулярними» системами поздовжніх ребер. Показано, що існування виявленого
раніше ефекта різкого зниження мінімальних власних частот коливань при визначених формах коли-
вань і малому числі ребер нe залежить від жорсткості ребер.